Exploring the self-efficacy beliefs among the high achievers in writing - Jalaluddin, Ilyana (Australian International Academic Centre, 2014)
Learners form their self-efficacy beliefs by interpreting information primarily from four sources namely performance accomplishments, vicarious experiences, verbal persuasion, and emotional arousal. It is important to recognize the four cognitive nature of self-efficacy because the cognitive appraisal of information from the four sources will influence self-efficacy and it cannot be evaluated based on one source per se (Lane, Jones & Stevens 2002). This article explores the four sources of self-efficacy among the high achievers in writing course. In analysing the finding, Z-scores were derived from each self-efficacy component score based on the aggregate mean and the standard deviation of the class. Findings show high frequency of negative z-value reported for Specific Progress (SPR) and Social Feedback (SF). Meanwhile, high frequency of positive z-value is found in the General Progress (GPR) and Physiological States (PS) components. Based on the finding, pedagogical implications, limitations and directions for further research are presented.